Conceiving the relationship between theory and practice in T-VET. : an in-depth study on key actors’ epistemological perspectives - Orozco, Mariana [Verfasser]; Gijbels, David [Verfasser]; Timmerman, Christiane [Verfasser] (My University, 2021)
"The integration of theory and practice constitutes an anchor of today’s technical vocational education and training (T-VET) and a major determinant of professional development. Understanding such integration is expected to contribute to pedagogical advancement and to provide new research tools. Current knowledge on the epistemological roots of pedagogical approaches is not automatically informative of the conceptions and beliefs of the students and their instructors in particular learning contexts. Therefore, if we are to disentangle further the theory-practice integration in T-VET, a first step is to grasp how these key actors conceive of theoretical and practical knowledge and the relationship between these kinds of knowledge. Thirty-eight subjects in dual T-VET in the field of chemical process technology, participated in serial and single focus groups. While adopting a grounded theory approach, the present qualitative study reveals the negotiated epistemological perspectives of students, school-instructors and workplace-instructors: forms of knowledge that respond to conceptions of theory or practice, the relationships between these forms of knowledge and the multiple agents who perform each connecting activity. The findings reveal a possible expression of the overall ‘integration of theory and practice’ as involving a network of relationships that are embodied by multiple agents. The implications are discussed." (Author's abstract ; BIBB-Doku)
Keywords: 370; Berufsbildung; Theorie-Praxis; Lernen am Arbeitsplatz; Grounded theory